The Principal's Strategy for Improving the Quality of Graduates at MIN 3 Nagan Raya - Supardi (Journal Informatic, Education and Management (JIEM), 2026)
The quality of graduates of Islamic elementary schools (madrasah ibtidaiyah) is an important indicator in measuring the success of Islamic-based elementary education institutions. The role of the madrasah principal is crucial in managing and developing appropriate strategies to improve the quality of graduates who are not only academically superior but also possess good morals and life skills. This study aims to analyze the strategy of the principal of Madrasah Ibtidaiyah Negeri (MIN) 3 Nagan Raya in improving the quality of graduates through the stages of planning, implementation, and evaluation. This study uses a qualitative approach with a case study method. Data collection techniques were carried out through in-depth interviews, direct observation, and documentation. Informants consisted of the madrasah principal, teachers, and education staff. The results show that the madrasah principal planned programs based on the madrasah's vision and mission, involved a solid work team, implemented structured quality improvement programs, and conducted continuous evaluations using the CIPP (Context, Input, Process, Product) model approach. This strategy successfully increased public trust, student skills, and graduate acceptance in further education institutions. This study recommends that madrasah principals continue to strengthen their transformational leadership capacity and conduct innovations based on regular quality evaluations.